EFFECT OF REPLACING COTTON SEED CAKE WITH SUNFLOWER MEAL ON MILK YIELD AND MILK COMPOSITION IN LACTATING NILI-RAVI BUFFALOES - M. A. Jabbar; I. B. Marghazani; Saima (Journal of Animal and Plant Sciences, 2009)
A feeding trial was conducted on thirty multiparous lactating Nilli-Ravi buffaloes to observe the effect of replacement of cottonseed cake with sunflower meal on their milk yield, milk composition and body weights. Thirty experimental animals were randomly divided in to three groups with similar stage of lactation. These animals were offered three different rations containing sunflower meal (SFM) and cottonseed cake (CSC) in the ratios 0: 48 (A-control), 18: 25 (B) and 39.5: 0 (C). All the rations were iso-nitrogenous and iso-caloric. Average daily milk production in buffaloes with rations A, B and C was 7.84 ± 2.06, 8.22 ± 2.05 and 7.35 ± 2.51 Kg respectively and difference was significant (P<0.05). Average body weights were recorded as 606 ± 64.49, 615.70 ± 80.82 and 591.50 ± 58.33 Kg in animals fed rations A, B and C respectively. The differences in fat percent in milk among three groups fed diets A, B and C were statistically significant (P<0.05), while the difference in solids-not-fat (SNF) and total solids (TS) percentage was non-significant. In a complementary experiment palatability of SFM in six Friesian x Sahiwal cross bred heifers was studied. The intake was 20.68, 17.50 and 24.68 kg/day in crossbred heifers receiving concentrate rations A, B and C, respectively showing higher palatability of sunflower meal compared to that of cotton seed cake.
Keywords: Cottonseed cake; sunflower meal; milk production; composition; Nili-Ravi buffaloes